The Ultrasound Methods of Distance Measurement for Working Equipment Control System of Mobile Machines - E.Y. Strock; L.D. Belchik; V.G. Nikiforov; V.N. Zinchenko (Механика машин, механизмов и материалов, 2008)
Development of plough control system using ultrasound equipment of distance measurement is presented. The experimental results confirm the efficiency of tractor performance with contactless sensor of soil profile copying.